Positions of Soviet secret service in totalitarian Soviet Union - Kristina Burinskaitė (Lietuvos Istorijos Studijos)
The Soviet secret service was one of the main pillars of the totalitarian Soviet system. The Bolshevik party formulated its policy according to communist ideology, where violence and dictatorship were among the most important elements. The Soviet secret service helped to implement their goals, consolidate Bolshevik power, and maintain the regime. But it did not implement just punitive and coercive functions; the Bolsheviks prescribed to them also political and ideological functions—to help the communist party implement its domestic and foreign policy, and to protect the communist system and ideology. Such functions made this institution exceptional in the USSR.